Experiential Learning in Teacher Education : Increasing Awareness of Diversity Through the Immersion Experience - Dolby , Nadine; Rahatzad , Jubin (Experiential Learning and Teaching in Higher Education, 2022)
Sixty-four years after the landmark Brown vs. Board of Educationdecision, schools, neighborhoods, and communities in the United States re-main largely segregated by race and class. As a result, many incoming studentsarrive on college and university campuses with limited exposure to people froma wide array of backgrounds and identities. In this article, we examine howstudents enrolled in an undergraduate teacher education course, Multicultur-alism and Education, learned from and reflected on an experiential learningassignment. The assignment, called “Immersion Experience,” required them tohave a brief experience in a cultural context that is different from their own.Through the assignment, students reflected on their own identities, values, andupbringing; learned about their stereotypes and beliefs about discrimination;and began to appreciate experience as a way of deepening their understandingof diversity. In an era in which undergraduates spend more of their time on-line, self-segregated and fractured by political beliefs and social identities andexperiences, assignments such as the “Immersion Experience” help to createthe physical, human encounters with difference that are vital for communityand democracy.